Climate Risk: Reshaping the Energy Sector - Sobik, Bartosz (Journal of Public Governance, 2023)
Objective: Climate risk is one of the major challenges for the energy sector globally. The energy transition and the struggle against climate change are putting increasing pressure on energy entities as well as create a need for action to mitigate climate risks. The purpose of this article is to characterise climate risk in the energy sector, with a focus on the electric power sector, as well as to review their impact on the functioning of energy entities. Research Design & Methods: This article reviews the literature and uses publicly available data on the operation of the electricity system and the price of CO2 emission allowances in the EU ETS so as to characterise the impact of climate risk on the energy sector with a particular focus on the Polish electricity sector. Findings: Climate risk is one of the most important risks determining the functioning of entities in the energy sector and affecting the energy transition. It manifests itself in the form of the emergence of a set of new risks: carbon risk, weather risk, financial risk, regulatory risk, and social risk, all of which directly affect energy operators and reshape the energy sector. Implications/Recommendations: The above creates the need to adapt and adjust to current market trends as well as the need to mitigate climate risks in order to keep a market position. It is, therefore, necessary to implement climate risk management measures to adapt the company’s operations to changing market realities and an increasing exposure to climate risk. The results of the study can be used by policymakers and decision-makers responsible for energy policy and companies’ strategy related to energy transition and compliance with the ESG standards. Contribution/Value added: The research contributes to the field of climate risk in the energy sector. The value added of the paper is the interdisciplinary approach to a broad concept of climate risk, consisting both of transition and physical risks, with a detailed analysis about its influence on the energy sector.